Penegakan Hukum terhadap Pelaku Penebangan Liar di Kawasan Konservasi Berdasarkan Undang-Undang Nomor 18 Tahun 2013 - Susan Srinovi; Hesti Dwi Astuti; Asep Hasanudin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Illegal logging in conservation areas constitutes a serious forestry crime that causes environmental degradation, biodiversity loss, and significant ecological and economic damage. Gunung Gede Pangrango National Park plays a strategic role in maintaining ecosystem balance and protecting biological natural resources; however, illegal logging activities continue to occur due to economic pressures, weak supervision, and limited public legal awareness. This study aims to analyze the implementation of law enforcement against perpetrators of illegal logging in conservation areas, identify obstacles encountered by law enforcement authorities, and examine conservation protection efforts based on Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction. The research employed a sociological-juridical method with descriptive-analytical specifications through normative and empirical approaches. Data were collected through library research, analysis of legislation, legal literature, and relevant court decisions. The findings indicate that law enforcement has been implemented through investigation, prosecution, and the imposition of criminal sanctions in accordance with applicable laws. Nevertheless, its effectiveness remains constrained by the limited number of forestry officers, extensive monitoring areas, low levels of legal awareness among local communities, and economic factors affecting residents surrounding forest regions. The study implies that stronger, integrated, and sustainable law enforcement measures, accompanied by community participation and preventive conservation policies, are essential to deter forest crimes and ensure the long-term preservation of conservation areas and environmental sustainability.